Synthesis of fluorescent C24-ceramide: evidence for acyl chain length dependent differences in penetration of exogenous NBD-ceramides into human skin - Novotný, Jakub; Pospechová, Katerina; Hrabálek, Alexandr; Cáp, Robert; Vávrová, Katerina (Bioorganic & medicinal chemistry letters, 2009)
Topical skin lipid supplementation may provide opportunities for controlling ceramide (Cer) deficiency in skin diseases such as atopic dermatitis or psoriasis. Here we describe the synthesis of a long-chain 7-nitrobenzo[c][1,2,5]oxadiazol-4-yl (NBD)-labeled Cer and its different penetration through human skin compared to widely used short-chain fluorescent Cer tools.
Keywords: permeabilita; Fluorescent Dyes; 4-chlor-7-nitrobenzofurazan; bisbenzimidazol; psoriáza; atopická dermatitida; Ceramides; kůže; Fluorescence; Permeability; 4-Chloro-7-nitrobenzofurazan; lidé; Dermatitis, Atopic; Psoriasis; Skin; ceramidy; Humans; Bisbenzimidazole; fluorescenční barviva; fluorescence